Concentration, market power and dynamism in the euro area - Maria Chiara Cavalleri; Alice Eliet; Peter McAdam; Filippos Petroulakis; Ana Cristina Soares; Isabel Vansteenkiste (European Central Bank (ECB), 2019)
We examine the degree of market power in the big four countries of the euro area using macro and firm-micro data. We focus on three main indicators of market power in and across countries: namely, the concentration ratios, the markup and the degree of economic dynamism. For the macro database we use the sectoral data of KLEMs and for the micro data we use a combination of Orbis and iBACH (dating from 2006 onwards). We find that, in contrast to the situation in the US, market power metrics have been relatively stable over recent years and - in terms of the markup specifically - marginally trending down since the late 1990s, driven largely by Manufacturing. In terms of the debate as to the merits of market concentration, we find (relying on results for Manufacturing) that firms in sectors which exhibit high concentration, but are categorized as 'high tech' users, generally have higher TFP growth rates. By contrast, markups tend to display a bi-modal distribution when looked at through the lens of high concentration and high tech usage. These results would tend to confirm that the rise in market power documented for other economies is not obviously a euro area phenomenon and that welfare and policy analysis of market concentration is inevitably complex.
Keywords: D2; D4; N1; O3; 330; Market Power; Euro Area; micro-macro data